Downregulation of OIP5-AS1 inhibits apoptosis in myocardial ischemia/reperfusion injury via modulating the MiR-145-5p/ROCK1 axis - Jingyan Yang; Jing Liu; Xiaobo Liu; Dongling Xu; Juan Zhang (PLoS ONE, 2025)
Purpose The role of Long noncoding RNA OIP5-AS1 in myocardial ischemia/reperfusion (I/R) injury-induced apoptosis remains to be fully elucidated. The present study was conducted with the objective of investigating the function of OIP5-AS1 in myocardial I/R injury and exploring its potential mechanisms. Methods In order to simulate the conditions of I/R, H9c2 cells were cultured in hypoxic/reoxygenated environments. Induction of I/R in Sprague-Dawley rats was achieved by ligating the left anterior descending coronary artery for 30 minutes followed by 180 minutes of reperfusion. OIP5-AS1 expression levels were assessed, and the degree of apoptosis was evaluated by TUNEL staining. Bioinformatic analysis was conducted to predict the interaction between microRNA-145-5p (miR-145-5p) and OIP5-AS1, and the expression levels of miR-145-5p and ROCK1 were determined. Results Elevated levels of OIP5-AS1 were observed in H/R-treated H9c2 cells and in rat I/R models. Elevated OIP5-AS1 expression was associated with an increased incidence of apoptosis. The silencing of OIP5-AS1 in I/R conditions resulted in a significant suppression of cell apoptosis, reduced cleavage of caspase-3, decreased Bax levels, and increased Bcl-2 levels. Bioinformatic analysis predicted binding sites between miR-145-5p and OIP5-AS1. Furthermore, depletion of OIP5-AS1 in I/R conditions resulted in a substantial increase in miR-145-5p expression and a decrease in ROCK1 expression. The suppression of miR-145-5p reversed the effects of OIP5-AS1 depletion in I/R conditions. Conclusions Downregulation of OIP5-AS1 may prevent apoptosis in myocardial I/R injury by modulating the miR-145-5p/ROCK1 axis.